Strain‐Promoted Cycloaddition of Cyclopropenes with o‐Quinones: A Rapid Click Reaction. (17th April 2018) - Gahtory, Digvijay; Sen, Rickdeb; Kuzmyn, Andriy R.; Escorihuela, Jorge; Zuilhof, Han
Abstract: Novel click reactions are of continued interest in fields as diverse as bio‐conjugation, polymer science and surface chemistry. Qualification as a proper "click" reaction requires stringent criteria, including fast kinetics and high conversion, to be met. Herein, we report a novel strain‐promoted cycloaddition between cyclopropenes and o ‐quinones in solution and on a surface. We demonstrate the "click character" of the reaction in solution and on surfaces for both monolayer and polymer brush functionalization.